Application of Dual Net-interface Card for Inverter Measuring System - XIE Chen-gang; CHEN Ming-kui; LI Xiao-wen; TAN Li-hong; LIU Wei-liang (机车电传动)
Dual net-interface card technology for solving LAN communication problems in inverter testing system was introduced in this paper. Replacing router by dual net-interface card, this method successfully achieved network communication among industrial control computer, control enclosure and measured DCU. Experiments results showed that with control enclosure and measured DCU installed service program, industrial control computer installed client program and IP addresses of dual net card configured in different network segments, data communication could be realize correctly. The technology has been applied in traction inverter measure system for Shenzhen metro line 5 vehicles.